2017
DOI: 10.1016/j.sste.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Exploring racial disparity in obesity: A mediation analysis considering geo-coded environmental factors

Abstract: Research shows aconsistent racial disparity in obesity between white and black adults in the United States. Accounting for the disparity is a challenge given the variety of the contributing factors, the nature of the association, and the multilevel relationships among the factors. We used the multivariable mediation analysis (MMA) method to explore the racial disparity in obesity considering not only the individual behavior but also geospatially derived environmental risk factors. Results from generalized line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…6 Rural Blacks have lower SES 14 and life expectancy 13 than both rural Whites and urban Blacks. Rural Blacks also have higher rates of the same chronic diseases that increase the risk of death should one contract COVID-19 (heart disease, diabetes, and respiratory diseases) [15][16][17][18][19][20] and shamefully low access to health care. 21,22 Blacks are also more likely to work in service occupations that require face-to-face contact with customers 23 and are more likely than Whites to live in multigenerational homes and with extended kin, 24 conditions that reduce the ability to socially distance and increase the risk of disease transmission.…”
mentioning
confidence: 99%
“…6 Rural Blacks have lower SES 14 and life expectancy 13 than both rural Whites and urban Blacks. Rural Blacks also have higher rates of the same chronic diseases that increase the risk of death should one contract COVID-19 (heart disease, diabetes, and respiratory diseases) [15][16][17][18][19][20] and shamefully low access to health care. 21,22 Blacks are also more likely to work in service occupations that require face-to-face contact with customers 23 and are more likely than Whites to live in multigenerational homes and with extended kin, 24 conditions that reduce the ability to socially distance and increase the risk of disease transmission.…”
mentioning
confidence: 99%
“…They also established the relationship between the proposed definitions of direct or indirect effect and the natural direct or indirect effect for binary exposure variables. Later, the definitions have been implemented to explore racial and ethnic health disparities by [ 19 , 20 ] and extended to deal with time-to-event outcomes ([ 21 ]) and for multiple exposures and multivariate outcomes ([ 22 ]). In this paper, we extend the method to the context of multilevel models.…”
Section: Third-variable Analysis With Multilevel Additive Modelsmentioning
confidence: 99%
“…Finally, we implement the method in a real data example: to explore the racial disparity in body mass index (BMI). In a previous research, we found that on average, non-Hispanic blacks have a higher BMI and higher rate of obesity compared with non-Hispanic whites [ 19 , 22 ] using the 2003-2006 National Health and Nutrition Examination Survey (NHANES). We are interested to see how the disparities can be explained by both individual and environmental factors.…”
Section: Explore the Racial Disparity In Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…It was first necessary to determine whether the ML models were adequately calibrated in 'test' cohorts different from the ML modeldiscovery 'training' cohorts. Controlling for age distribution, geographic differences, gender, common contraindications for the treatment-of-interest (discharge beta-blocker post-CAB), and other factors [34][35][36][37][38][39][40][41][42] is important, to insure adequate statistical power for these assessments and to mitigate confounding [27,43]. Establishing that the ML model was adequately well-calibrated for each racial group prior to performing procedures to evaluate the presence of discrimination or disparities was performed using the Hosmer-Lemeshow test by model score deciles.…”
Section: Evaluation Approachmentioning
confidence: 99%